APLIKASI AKUNTANSI PENJUALAN WEB-BASED - Fithri, Eka Jumarni; Ardiani, Susi; Mubarok, Muhammad Husni (Jurnal Pengabdian Masyarakat Akuntansi, Bisnis & Ekonomi, 2023)
A business generally aims to get the maximum profit. Coaching in the use of the Web-Based Sales Accounting Application is carried out to assist business owners in managing their business so that they are able to develop. The internet is a global computer network that can connect all users with a wide network throughout the world to exchange information quickly, precisely and accurately. The lack of understanding of small businesses regarding the use of process technology in achieving sometimes makes marketing reach only limited in the business environment, while during a pandemic like this it makes consumers more comfortable making purchases online to reduce the risk of spreading epidemics. This limitation of space and movement of community activities makes technological developments growing rapidly, so that the competition between one company and another is getting tougher, especially companies that produce similar goods. The limited scope of this business will affect the profits obtained so that it attacks small businesses in competing with similar businesses. The method to be used in solving partner problems is carried out through several stages, namely 1. Preparation 2. Demonstration 3. Practice and Guidance 4. Technical Consultation Services 5. Program Evaluation 6. Report on Activity Results Keywords: Web-Based, Sales Accounting Application